2020
DOI: 10.3390/ijms21051730
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the In Vivo Inflammatory Response by Pro- Versus Anti-Inflammatory Intervertebral Disc Treatments

Abstract: Inflammation is central in intervertebral disc (IVD) degeneration/regeneration mechanisms, and its balance is crucial to maintain tissue homeostasis. This work investigates the modulation of local and systemic inflammatory response associated with IVD degeneration/herniation by administration of PRO-versus ANTI-inflammatory treatments. Chitosan/poly-γ-glutamic acid nanocomplexes, known as pro-inflammatory (PRO), and soluble diclofenac, a non-steroidal anti-inflammatory drug (ANTI), were intradiscally administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
1
14
0
1
Order By: Relevance
“…These hydrogels are mainly derived from non-degradable polyacrylates and polyacrylamides [ 10 , 11 ] and degradable hyaluronic acid, collagen in the extracellular matrix and chitosan [ 8 , 12 ]. However, these implanted materials often failed to regulate the post-injury microenvironment, and tissue degeneration, water loss and inflammatory reaction often appeared in situ [ 13 , 14 ]. Regarding AF, structural repair is a hot spot.…”
Section: Introductionmentioning
confidence: 99%
“…These hydrogels are mainly derived from non-degradable polyacrylates and polyacrylamides [ 10 , 11 ] and degradable hyaluronic acid, collagen in the extracellular matrix and chitosan [ 8 , 12 ]. However, these implanted materials often failed to regulate the post-injury microenvironment, and tissue degeneration, water loss and inflammatory reaction often appeared in situ [ 13 , 14 ]. Regarding AF, structural repair is a hot spot.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the context of cell therapy, restoring the hypoxic microenvironment may favour the use of NP progenitor cells. E x c e s s i v e m e c h a n i c a l l o a d i n g a n d impaired biomechanics can be another crucial microenvironmental factor influencing NP progenitor behaviour (Chu et al, 2018;Desmoulin et al, 2020). For example, several studies showed an essential correlation between the presence and the severity of disc degeneration in obese or overweight adults (Lidar et al, 2012;Samartzis et al, 2012).…”
Section: Influences Of Non-ecm Related Factors On Ivd Progenitor Cellsmentioning
confidence: 99%
“…One aspect is the application of drugs. In addition to analgesics, which with their low molecular weight are often used as a first resort to relieve LBP associated with IVD degeneration, various novel treatments are also being evaluated in preclinical models (Cherif et al, 2020;Cunha et al, 2020;Hu et al, 2019;Wang et al, 2020a). Among these, inflammatory cytokine and enzyme inhibitors are frequently used as therapeutic agents, but so far these agents have shown no or only limited effectiveness and an increased risk of adverse events (Tryfonidou et al, 2020).…”
Section: Drugsmentioning
confidence: 99%
“…A decrease in the AF cell density, as frequently observed in degenerated IVDs, alters the balance of anabolism:catabolism ratio in the extracellular matrix (ECM), changing the AF mechanical, biological, and structural properties [ 69 , 70 , 71 ]. Therefore, regenerative strategies aim to repopulate a degenerated IVD with healthy cells (cell therapy) or stimulating the existing cells to regulate the ECM reaching an enhanced composition, quantity, and structure (biomolecule and gene therapy) [ 81 , 82 , 83 , 84 , 85 ]. ECM remodeling is crucial to control the action of biochemical mediators such as cytokines (interleukins), growth factors, and enzymes (metalloproteinases and heparanase) to ultimately stop or reverse the IVD degeneration process [ 86 , 87 , 88 , 89 ].…”
Section: Regenerative Strategiesmentioning
confidence: 99%